Immobilization of CALB on lysine-modified magnetic nanoparticles: influence of the immobilization protocol - Nicolás, Paula; Lassalle, Verónica Leticia; Ferreira, María Luján (Bioprocess and Biosystems Engineering)
Magnetic biocatalysts offer enormous advantages over traditional ones. Their ability to be isolated by means of a magnet, in combination with their extensive reuse possibilities, makes them highly attractive and competitive from the commercial point of view. In this work, magnetic biocatalysts were prepared by immobilization of Candida antarctica Lipase B (E.C. 3.1.1.3, CALB) on magnetite–lysine nanoparticles. Two methodologies were explored tending to find the optimal biocatalyst in terms of its practical implementation: I—physical adsorption of CALB followed by cross-linking, and II—covalent coupling of the lipase on the nanoparticles surface. Both procedures involved the use of glutaraldehyde (GLUT) as cross-linker or coupling agent, respectively. A range of GLUT concentrations was evaluated in method I and the optimum one, in terms of efficiency and operational stability, was chosen to induce the covalent linkage CALB-support in method II. The chosen test reaction was solvent-free ethyl oleate synthesis. Method I produced operationally unstable catalysts that deactivated totally in four to six cycles. On the other hand, covalently attached CALB (method II) preserved 60% of its initial activity after eight cycles and also retained 90% of its initial activity along 6 weeks in storage. CALB immobilization by covalent linkage using controlled GLUT concentration appears as the optimum methodology to asses efficient and stable biocatalysts. The materials prepared within this work may be competitive with commercially available biocatalysts. Fil: Nicolás, Paula. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto de Química del Sur. Universidad Nacional del Sur. Departamento de Química. Instituto de Química del Sur; Argentina Fil: Lassalle, Verónica Leticia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Instituto de Química del Sur. Universidad Nacional del Sur. Departamento ...